CULTURAL SEMIOTICS: AN EXAMINATION OF TICUNA SYMBOLIC REPRESENTATIONS AS RESILIENCE OF INDIGENOUS KNOWLEDGE SYSTEMS - Pinto, Maria Auxiliadora Coelho; Souto, Caio Augusto Teixeira; Justamand, Michel; Nunes, Claudia Ribeiro Pereira (Seven Editora, 2025)
This study investigates Cultural Semiotics through the symbolic representations of the Ticuna people, one of the largest Indigenous nations in Brazil, with emphasis on the community of São Leopoldo, Amazonas. It seeks to understand how the Ticuna articulate their cosmology, memory, and identity through cultural and iconographic personifications of nature. The research adopts a qualitative approach, conducted through fieldwork in collaboration with five Ticuna interlocutors possessing extensive knowledge of their collective heritage. Data collection emphasized oral narratives and cultural practices, focusing on the symbolic and iconographic dimensions embedded in the Ticuna worldview. The findings reveal that the Ticuna preserve remarkable cultural vitality by maintaining their native language, traditions, and interpretive worldview. Nature represented through the earth, rivers, trees, wind, mountains, and other phenomena is personified as anthropomorphic, phytomorphic, and zoomorphic beings, which embody divine, heroic, and demonic attributes. These symbolic representations are central to the mythical universe of the Magüta and remain deeply embedded in the cultural identity and collective memory of the Ticuna. The study demonstrates that cultural semiotics provides an essential framework for documenting and safeguarding Indigenous symbolic systems. By recording the personifications of natural and cosmic elements, the research contributes to the protection of the Ticuna intangible heritage and offers a deeper understanding of Amazonian Indigenous worldviews. Furthermore, it highlights the broader role of cultural semiotics in reinforcing the resilience of Indigenous knowledge systems within contemporary debates on cultural preservation. DOI: https://doi.org/10.56238/sevened2025.029-121